Namibian ally? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
African countries with hot, arid climates or even those with waterlogged or salty clay soils may have an ally in a versatile tree species found in Namibia. Terminalia sericea has spread naturally over a former war-zone area that had been cleared...